Analisis Tingkat Pendidikan dan Pemanfaatan Digitalisasi Terhadap Penerapan Manajemen Keuangan Syariah pada UMKM di Kecamatan Ciamis - Nurjannah, Lastri Apriani (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2023)
Financial management is very necessary for MSMEs as an effort to control assets or funds and carry out financial planning to increase profitability. This study aims to determine the relationship between the Education Level and the use of digitalization on Islamic financial management for MSME actors in Ciamis District. The method used in this study is a quantitative method using primary data through questionnaires on MSME actors. Research sample with a total of 100 respondents. This research method uses multiple linear regression method. The results showed that the level of education and the use of digitalization have a positive and significant relationship with Islamic financial management, the use of digitalization has a significant positive relationship with Islamic financial management for MSME players in Ciamis District. This shows that the higher the level of education and the use of digitalization of MSME actors in Ciamis District, the more the application of Islamic financial management for MSME actors in Ciamis District will increase